Advanced Colonoscopy and Endoluminal Surgery - Lee, Sang W.; Ross, Howard M.; Rivadeneira, David E.; Steele, Scott R.; Feingold, Daniel L. (Springer International Publishing : Imprint: Springer, 2017)
Each chapter of this new book on advanced lower GI endoscopy and endoluminal surgery focuses on the thought process and step-wise technical approach to the condition and procedure listed. By using this unique method, practitioners ranging from surgeons-in-training, gastroenterologists-in-training and those early in their career to senior colorectal specialists and gastroenterologist who want to incorporate or improve their advanced endoscopic skills will be able utilize techniques and learn from this gathering of experts. The guiding principle of this work is to create a resource for surgeons and gastroenterologists that extends beyond the currently available texts, and that surgeons and gastroenterologists can turn to when wanting to "brush up" on techniques, find a useful "tip or trick" for a complex patient, or simply learn a reproducible methods for advanced endoscopic procedures. This unique book highlights current knowledge, demonstrates standards of medical care, and provides clear step-by-step reproducible techniques even for the most advanced procedures. Beyond the simple application of technical knowledge the book addresses the deeper questions about the optimal "next step" in dealing with more complex patients. International experts also address future challenges and innovations in lower gastrointestinal endoscopy. Finally, it focuses on specific "tips and tricks" that experts in the field have learned. The format follows that of both a "how to" manual as well as an algorithm-based guide to allow the reader to understand the thought process behind the proposed treatment strategy. Throughout the text, each author provides an ongoing narrative of his/her individual techniques along with color illustrations and diagrams to "personally" take the reader through the crucial steps of the procedure, and key points of patient care inherent to that topic. Additionally, where appropriate, links to online videos will give the reader an up-front look into technical aspects of EMR, ESD, endoscopic stent placements, CELS, as well as NOTES. This book will be useful to colorectal surgeons, general surgeons, and gastroenterologists who want to learn or improve their skills in lower gastrointestinal endoscopy and advanced endoscopic interventions. Furthermore, this book will be of particular interest to the surgeons-in-training, and gastroenterologist-in-training that are often called upon to manage a variety of colorectal conditions through an endoscopic approach.
Keywords: Medicine.; Gastroenterology.; Rectum -- Surgery.; Surgery.; elektronické knihy; electronic books